Development of Sustained Release Oseltamivir Phosphate Dry Powder Inhaler: In-Vitro Characterization and In-Vivo Toxicological Studies - Sahastrabudhe, Harshal; Kenjale, Prathmesh; Pokharkar, Varsha (Current Drug Delivery, 2020)
Background: Oseltamivir Phosphate (OP) is an ethyl ester prodrug prescribed for the treatment of influenza virus infection. Current marketed formulations of OP have been observed to be supplemented with an adverse effect during post-marketing surveillance. These prerequisites are sufficed by developing a sustained release Dry Powder for Inhalation (DPI). Objective: The objective of the present study was to develop OP-DPI by an innovative formulation approach comprising of Immediate (IR) and Sustained (SR) Release portions. Methods: DPI formulation comprising IR and SR portions were prepared by spray drying technique using Hydroxy Propyl Methyl Cellulose (HPMC) as the rate-controlling polymer for SR portion. The spray-dried product was further characterized for various pharmaco-technical, in-vitro and in-vivo parameters. Results: OP-DPI showed a burst release of 49% within 15 min further sustaining the drug release up to 9 hrs. The in-vitro aerodynamic performance of OP-DPI showed maximum deposition at stage 3 and Fine Particle Dose (FPD) of 1.08 mg indicating deposition in the upper respiratory tract. Solid-state characterization by DSC and XRD indicated the partial amorphization of OP due to spray drying. In-vivo toxicological examination revealed no sign of inflammation, indicating the safety of the developed formulation. Accelerated stability study as per ICH guidelines displayed no significant change in the solid-state characterization and drug-related performance of OP-DPI. Conclusion: Prepared novel and scalable OP-DPI may have the potential to overcome the problems associated with existing marketed dosage forms of OP. Further, localized drug delivery of the antiviral drug through the pulmonary route might be clinically beneficial in controlling the viral proliferation.
Keywords: particle engineering